Synthesis, Characterization and Antimicrobial Activities of Mixed Ligand Complexes of Fe (II), Co(II), Ni(II) and Cu (II) Ions Derived from Imine of Benzidine and o-phenylenediammine - Mihsen, Hayder Hamied; Abass, Suhad Kareem; Abed –Alhasan, Maysaa Taqe; Hassan, Zainab M.; Abass, Ali Kreem (Iraqi Journal of Science, 2020)
Binuclear metal complexes of the metal ions Fe (II), Co (II), Ni (II) and Cu (II) were synthesized by the reaction of these metal ions with the imine of benzidine (H2L) as a primary ligand and o-phenylenediammine (OPD) as a secondary ligand in a molar ratio of 2:2:1. The prepared complexes were characterized using CHN elemental analysis, FT-IR, UV-visible, molar conductivity, magnetic susceptibility and TGA-DTA thermogravimetric analysis. All the prepared complexes showed apparent stability and could be stored for months without any appreciable change. According to the results obtained by elemental and spectral analyses, a tetrahedral structure is suggested for all the prepared complexes, except for the copper complex which showed a square planar structure. The antimicrobial activities of these complexes were evaluated against Bacillus spp. (Gram-negative bacteria), Proteus spp. (Gram-positive bacteria) and Aspergillus niger (A. niger, a fungal species). The results showed that all the prepared complexes have no apparent effects on Bacillus spp. viability, whereas Proteus spp. and A. niger were affected significantly.